ChemInform Abstract: Spectroscopic Analysis of the Interaction of Human Serum Albumin with Tricationic Phosphorus Porphyrins Bearing Axial Pyridinio Groups. Issue 3 (21st January 2014) - Matsumoto, Jin; Kubo, Tomoya; Shinbara, Tomohiko; Matsuda, Naomi; Shiragami, Tsutomu; Fujitsuka, Mamoru; Majima, Tetsuro; Yasuda, Masahide
Abstract Review: 37 refs.